1998
DOI: 10.1002/(sici)1521-4141(199805)28:05<1554::aid-immu1554>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

CD28 co-stimulation is intact and contributes to prolongedex vivo survival of hyporesponsive synovial fluid T cells in rheumatoid arthritis

Abstract: In rheumatoid arthritis (RA), T cells in the inflamed joint are considered to play a crucial role in the pathogenesis. However, despite the fact that synovial T cells have an activated memory phenotype, they are functionally suppressed upon combined CD3 and CD28 stimulation. Here, we analyzed the contribution of both CD3 and CD28 to the hyporesponsiveness of synovial T cells in RA. In contrast to the low CD3 responsiveness of synovial fluid (SF) T cells compared to peripheral blood (PB) T cells, the CD28 co-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…Using intracellular FACS staining, it was observed that synovial T cells expressed low levels of antiapoptotic Bcl-2 (41). Under these circumstances, it was proposed that synovial T cell apoptosis in situ was actively suppressed by cell-cell contacts, signaling of IL-2 and IL-15 via the IL-2 receptor common ␥-chain, and/or CD28 costimulation, each of which could enhance Bcl-x L protein expression (41,42,57). In our analysis of mRNA expression in RA SF T cells, we did observe a modest decrease in Bcl-2 expression, but no differences in Bcl-x L expression, compared with HD and RA PB T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using intracellular FACS staining, it was observed that synovial T cells expressed low levels of antiapoptotic Bcl-2 (41). Under these circumstances, it was proposed that synovial T cell apoptosis in situ was actively suppressed by cell-cell contacts, signaling of IL-2 and IL-15 via the IL-2 receptor common ␥-chain, and/or CD28 costimulation, each of which could enhance Bcl-x L protein expression (41,42,57). In our analysis of mRNA expression in RA SF T cells, we did observe a modest decrease in Bcl-2 expression, but no differences in Bcl-x L expression, compared with HD and RA PB T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the observed discrepancy between RA SF T cell proliferative and cytokine responses in bulk cultures and single-cell analyses could be changes in RA SF T cell viability, as these cells have been reported to quickly undergo apoptosis ex vivo (41,42). Assays using [ 3 H]thymidine incorporation and tissue culture supernatant ELISA analyses cannot accurately account for apoptosis which may occur during extended cell culture.…”
Section: Ra Sf T Cell Hyporesponsiveness In Bulk Cultures Is Secondarmentioning
confidence: 99%
“…We therefore turned our attention to the possible role of CD28 in this process, since we and other investigators have previously demonstrated that CD28 costimulatory signaling can block T cell Rap1 activation via RapGAP I (27,28). In addition, CD28 signaling pathways, as opposed to those of CD3, have been reported to be intact in RA SF T lymphocytes (29).…”
Section: Induction Of Mitogenic Hyporesponsiveness In Pbmentioning
confidence: 99%
“…This indicates that 17 and with acute and chronic viral infections 18,19 including HIV, 20,21 in T cells from patients with allogeneic bone 22 and in synovial T cells from joints affected with rheumatoid arthritis. 23,24 Supplementation of Tcell cultures with IL-2R g-chain cytokines upregulates Bcl-2 and Bcl-xL expression and decreases the number of apoptotic cells in vitro implying that cytokine deprivation may be responsible for accelerated apoptosis of these cells. 25,26 Whereas IL-15 is active, IL-2 in concentrations of 1 ± 10 nM, in contrast, fails to rescue CD4 + CD7 7 T cells from apoptosis in vitro.…”
Section: Accelerated Apoptosis Of Cd4mentioning
confidence: 99%